Characterization of sampling artifacts in the measurement of carbonaceous particles using high- and low-volume samplers in Daejeon, Korea. (August 2016) - Kim, Doyeon; Jung, Jinsang; Lee, Hyoeun; Choi, Seong-Ho; Lee, Sangil; Oh, Sanghyub
Abstract: This study investigates the influence of positive sampling artifacts on the determination of atmospheric organic carbon (OC) and elemental carbon (EC) by undenuded high-volume (HV) and low-volume (LV) samplers. The samples, which were collected in Daejeon, Korea during the spring and fall of 2014, were analyzed for OC and EC using a thermal optical transmittance (TOT) technique. Positive artifacts for OC using the undenuded LV and HV samplers were determined to be ∼12.2% and ∼7.2%, respectively. The adsorption of organic vapors on quartz filters and the analytical artifacts of thermal-optical method contributed equally to the positive artifact for the HV sampler, whereas that of the undenuded LV sampler was caused primarily by the adsorption of organic vapors on quartz filters with a relatively small contribution from the analytical artifacts of thermal-optical method. The analytical artifacts of thermal-optical method was closely related to the additional formation of pyrolyzed OC (POC) during the analysis, resulting in an underestimation of EC (HV sampler: 15.6 ± 15.6%; undenuded LV sampler: 9.1 ± 7.6%). The POC that formed during the analysis was related to the adsorption of organic vapors (in both the HV and undenuded LV samplers) and high particle loading on the quartz filters (HV sampler only). OC concentrations determined using the undenuded LV sampler and corrected using backup filter measurements correlated well with those of the denuded LV sampler (R 2  = 0.98), suggesting that the backup filter correction method can be applied to particulate OC measurements using an undenuded LV sampler under conditions typical of those in Daejeon, Korea. Graphical abstract: Highlights: Positive artifacts for OC using the undenuded low-(LV) and high-volume (HV) samplers were ∼12.2% and ∼7.2%, respectively. Adsorbed organic vapors and the analytical artifacts contributed equally to the positive artifact for the HV sampler. The formation of pyrolyzed OC for HV sampler was related to the adsorption of organic vapors and high particle loading.